The small world of editorships: A network on innovation studies - Santos, A. T.; Mendonça, S. (18th International Conference of the International Society for Scientometrics and Informetrics, 2021)
Editors exert a significant influence on journal's mission and governing the strategic direction of outlets. They are the channels gatekeepers not only by ensuring the quality but also by guaranteeing the integrity of novels produced. For being such an important piece of scientific puzzle, they are a research object of utmost interest which is rather fragmented. This paper aims to better understand the relationships between editors seated on boards of 20 innovation top-tiers. The sample considered comprised 2,440 editors occupying 3,005 editorial positions and assuming 122 different duties. No single journal is free from this interlocking editorship phenomenon and 18.6% of the scholars serve on multiple boards. We deploy social network analysis to further inquire and model the editorial relationships in which innovation journals are embedded. Our results offer new insights on how the field is organised: 627 lines linking the journals were found with a 41.6% interlocking density. Research Policy has the highest number of direct links to other boards (degree) and the shortest distance from all network journals (closeness) while Industrial and Corporate Change is the one bridging the largest number of other pairs of journals (betweenness), followed by Small Business Economics and Research Policy.